MEMBANGUN KOMUNITAS HIJAU MELALUI PELATIHAN “PROGRAM SADAR PRODUK HIJAU MELALUI MEDIA SOSIAL” PADA GENERASI MILENIAL DI LAMPUNG - Wangsa, Ignasius Heri Satrya; Josephine Tyra, Maria; Lina, Lina; Riyanto, Agustinus; Gunady Ony , Johan; Fernando, Agustinus (Universitas katolik Musi Charitas, 2023)
The coming of the digital era opens up new opportunities for social media as an interactive means ofaccumulating knowledge. Individuals who interact with each other in social media space operate thecapacity of information-seeking and information-sharing. At a certain level, the accumulation ofknowledge formed by the information-seeking and information-sharing activities of social media opensup views for solving practical problems, including one of which is environmental problems. By usingthe global normal argument of green practices and the potential of the millennial generation inIndonesia, the Tim Pengabdian kepada Masyarakat (PkM) of Universitas Katolik Musi Charitas -Palembang held an activity entitled